2020
DOI: 10.5334/aogh.2912
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence, Predictors, and Characteristics of Waterpipe Smoking Among Jazan University Students in Saudi Arabia: A Cross-Sectional Study

Abstract: Introduction Waterpipe smoking (WPS), which is otherwise called shisha, narghile, and Gozaor hookah, has been one of the most common strategies for tobacco use in developing nations for approximately 400 years [1-4]. Its device consists of a head, body, water bowl, and hose [5]. WPS contains tobacco-specific nitrosamines and glycerol nicotine, which are derived from raw materials, and it produces chemical substances (such as carbon monoxide (CO)), which are synthesised during smoking, and produces 34 polyaroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…In a recent study conducted by Salih et al 29 among university students in Jazan, Saudi Arabia, 50% of the participants said that smoking shisha with flavors, such as apple, makes it less dangerous than with flavorless. According to the review article of Qasim et al 30 , flavored tobacco, which gives the user a pleasant taste and aroma, also plays a vital role as a ‘motivator’ for consuming shisha.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study conducted by Salih et al 29 among university students in Jazan, Saudi Arabia, 50% of the participants said that smoking shisha with flavors, such as apple, makes it less dangerous than with flavorless. According to the review article of Qasim et al 30 , flavored tobacco, which gives the user a pleasant taste and aroma, also plays a vital role as a ‘motivator’ for consuming shisha.…”
Section: Discussionmentioning
confidence: 99%
“…Our results corroborate those of several authors. Salih et al, reported a prevalence of 42.5% of male and 27% of female students at the University of Jazon in Saudi Arabia [8]. The work of Primack et al, reported that women were more attracted to the milder flavoured types of tobacco marketed as more social and exotic than shisha flavour [9].…”
Section: Socio-demographic Characteristics Of the Users And The Psychoactive Substances Consumed By Means Of Shishamentioning
confidence: 99%
“…The results showed that nicotine elevates the expression of RAGE in GECs, which reflects that AGEs-RAGE communications are linked with the etiopathogenesis of periodontitis in smokers [ 10 ]. Waterpipe (also known as narghile, hubble-bubble or/and hookah) is another form of tobacco-smoking, which is a cultural norm in many Middle-Eastern countries such as Kuwait and Saudi Arabia [ 21 24 ]. However, habitual use of waterpipe is now prevalent in many European countries and the United States [ 25 27 ].…”
Section: Introductionmentioning
confidence: 99%